Efficacy of routine diabetic foot treatments at an outpatient clinic: a cohort study - Oleg Viktorovich Udovichenko; Eugenia Alexandrovna Berseneva (Сахарный диабет)
Reliable data on the efficacy of treatment for diabetic foot (DF) ulcers (DFUs) is essential for planning outpatient services, comparison of several DF clinics, pharmacoeconomic studies and prognosis of healing time. However, no reports based on Russian DF cases have been published to date.Aim. The aim of our study was to analyse of the outcomes of routine DFU treatments at one DF outpatient clinic (DFOC).Materials and methods. We analysed the medical records of all patients admitted to one DFOC for foot/leg ulcers in 2012 (72 patients, 77 episodes of treatment, 124 ulcers in total). The median age of the patients was 66 years (range: 45?90 years), 51% patients were females and 49% were males. Three (4%) patients had type 1 diabetes mellitus, whereas the rest had type 2 diabetes mellitus. The median duration of ulcer prior to the initiation of treatment was 31 days (range: 1?392 days). A total of 106 (85%) cases involved DFUs, whereas 18 (15%) involved leg ulcers in patients with diabetes. One patient had a combination of foot and leg ulcers. Examination and treatment of all patients were conducted by a single experienced doctor according to international and national guidelines. The follow-up time ranged from 8?20 months.Results. Lower extremity ischemia was observed in 39% cases. The healing rate for all ulcers at 3, 6 and 12 months was 34%, 51% and 65%, respectively. At follow-up time, ulcers remained unhealed in 16% patients and 9% survived amputations [1 (1%), below knee; 6 (8%), minor)]. Furthermore, 4% patients died on account of cardiovascular events. The results of the present study were comparable to those reported in other countries. Modern and effective treatment modalities (such as contact casting and revascularisation) were not used extensively; therefore, their active utilisation is necessary to improve treatment outcomes.Conclusions. The healing rate for ulcers in our cohort was 34%, 51% and 65% at 3, 6 and 12 months, respectively. Treatment efficacy should be improved by increasing the use of total contact casting and revascularisation. Person-related measures (i.e. healing of all ulcers in a patient) are optimal for most cases, although ulcer-related measures can be significant in cases where several ulcers are detected in a patient. Our studied cohort is typical for a DFOC; therefore, our data can be used for planning outpatient services, evaluation of other DFOCs and pharmacoeconomic studies.